Formation and Analysis of Cobalt (III) with a Tetradentate N,N,O,O-Donor Ligand and 2,2’-Propane-1,2-diyl-bis[Nitrilo(E) Methylidene]bis(6-Methoxyphenol) - Alassane Saidou Diallo; Mariama Sarr; Mbosse Ndiaye Gueye; Antoine Blaise Kama; Farba Bouyagui Tamboura; Ibrahima Elhadj Thiam; Moussa Dieng; Mohamed Gaye (Chemical and Materials Sciences: Developments and Innovations Vol. 10, 2025)
For a long time, chelating agents derived from organic compounds containing N,S,O-donor as a functional group have a strong ability to form metal complexes and exhibit a variety of biological activities. A number of studies have been done on the various Schiff base complexes formed by the condensation of secondary amines with different aldehydes and ketones. Schiff bases have often been used as chelating ligands in the field of coordination chemistry, and their metal complexes have been extensively investigated due to their potential applications. It is known that reactions of N,N,O,O-donor Schiff base ligands with transition metal ions have produced a series of complexes with interesting structures and magnetic properties. A new complex prepared by the reaction of 2,2’-propane-1,2- diyl-bis[nitrilo(E)methylidene]bis(6-methoxyphenol) (H2L) with Co(III) ion is reported in this paper. The bicompartmental ligand acts in a tetradentate fashion. The H2L ligand is structurally characterized by elemental analysis, NMR and infrared spectroscopies, conductance and single X-ray diffraction. The compound with Co(III) crystallizes in the monoclinic system in the space group P21/c with the unit cell parameters a = 13.168(2) Å, b = 15.795(2) Å, c = 15.882(2) Å, \(α\) = 90°, \(β\) = 110.703(16)°, \(γ\) = 90°. The cobalt (III) ion has a slightly distorted octahedral coordination geometry.